Tinjauan Pertanggungjawaban PT. Lapindo Brantas Berdasarkan Aspek Responsibility Theory dengan UU No 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup - Fadhilatul Amaliya; Anindya Rahma Fathiya; Tiara Jelita Andalusianti Roozan; Isna Nurul Hasanah; Dewi Sekar Pembayun (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The Lapindo Brantas case is the largest environmental disaster in Indonesia, causing significant environmental damage and widespread economic and social impacts on the surrounding community. This incident sparked debate about corporate legal responsibility for the damage that occurred. This study aims to thoroughly evaluate the responsibility of the Lapindo Brantas corporation using the responsibility theory approach and Law Number 32 of 2009 concerning Environmental Protection and Management. The methods used are normative with case studies and legislative analysis to understand the mechanism of corporate legal responsibility in the context of environmental disasters. The findings of this study indicate that corporations can be held criminally liable for environmental damage, and in the case of Lapindo Brantas, the company bears legal responsibility in accordance with the principle of strict liability as stipulated in Law Number 32 of 2009. This study emphasizes the urgency of applying the principle of corporate responsibility as an important part of environmental law enforcement in Indonesia.